2007
DOI: 10.1073/pnas.0700668104
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological signatures of resting state networks in the human brain

Abstract: Functional neuroimaging and electrophysiological studies have documented a dynamic baseline of intrinsic (not stimulus-or task-evoked) brain activity during resting wakefulness. This baseline is characterized by slow (<0.1 Hz) fluctuations of functional imaging signals that are topographically organized in discrete brain networks, and by much faster (1-80 Hz) electrical oscillations. To investigate the relationship between hemodynamic and electrical oscillations, we have adopted a completely data-driven approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

168
1,623
10
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,761 publications
(1,837 citation statements)
references
References 53 publications
(134 reference statements)
168
1,623
10
5
Order By: Relevance
“…These findings are consistent with our observations that decreased metabolic rate is accompanied by decreased a band (8 to 13 Hz) power and increased d band (1 to 3 Hz) power. The relationship between fcMRI and EEG signals has also been studied by a number of investigators, and the majority of the reports appear to suggest that fcMRI signal has a correlation with a power in the EEG (Mantini et al, 2007;Moosmann et al, 2003). Thus, our observation of a concomitant reduction in fcMRI signal and a power during hypercapnia is in general agreement with this notion.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with our observations that decreased metabolic rate is accompanied by decreased a band (8 to 13 Hz) power and increased d band (1 to 3 Hz) power. The relationship between fcMRI and EEG signals has also been studied by a number of investigators, and the majority of the reports appear to suggest that fcMRI signal has a correlation with a power in the EEG (Mantini et al, 2007;Moosmann et al, 2003). Thus, our observation of a concomitant reduction in fcMRI signal and a power during hypercapnia is in general agreement with this notion.…”
Section: Discussionsupporting
confidence: 87%
“…Using such methods, several studies have examined the association between fluctuations in the frequency power of spontaneous EEG activity and BOLD signals obtained using fMRI (Goldman et al, 2002;Jann et al, 2009;Laufs et al, 2003;Mantini et al, 2007;Tyvaert et al, 2008). These studies have revealed that oscillations in the different frequency bands contribute differentially to the BOLD signal.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The functional organization of the brain at rest is currently conceived in terms of resting state networks (RSNs), clusters of brain regions, mostly cortical, inter-connected anatomically and functionally (Beckmann et al 2005;Damoiseaux et al 2006;Fox and Raichle 2007;Mantini et al 2007; van den Heuvel et al 2008). The study of RSNs has shifted the focus in neuroimaging from the exact localization of specialized brain functions (looking for "things in a place") to the understanding of the interplay of widespread brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study of RSNs by EEG, biophysical and neurophysiological studies suggest that each RSN may exhibit complex dynamic associated with multiple frequencies simultaneously (Mantini et al 2007). Studying the distribution of scalp EEG power at rest, as in Chen et al (2008), does not allow the study of RSNs by EEG because scalp voltage is a mixing of underlying source activity (volume conduction: see Nunez and Srinivasan 2006) and because scalp power is not a comprehensive measure of widespread coherent synchronization.…”
Section: Introductionmentioning
confidence: 99%